Ruptured Tubal Triplet Heterotopic Pregnancy After in Vitro Fertilisation: A Case Report - Osmanağaoğlu, Mehmet; Aksoy, Murat; İlhan, Ceylan and Erin, Recep (Gynecology Obstetrics & Reproductive Medicine, 2011)
To analyse the incidence, diagnostic and therapeutic management of heterotopic pregnancy following in vitro fertilisation (IVF). We present a case who had a ruptured left tubal heterotopic triplet pregnancy at nine weeks of gestation following in vitro fertilisation. A 47-year-old pregnant woman who conceived following IVF-ET transfer was referred to our emergency unit with a suspicion of stomach perforation at 9 weeks’ gestation. on physical examination she had severe abdominal pain and distension. Her blood pressure 130/70 mmHg and pulse rate 96 beats/min. Pelvic examination showed tenderness on movement of the cervix and a slightly enlarged uterus. Her hemoglobin was 9.4 mg/dl. Transabdominal ultrasound examination showed an intrauterin viable twin pregnancy. A third gestationel sac at the left cornual area of which diameter was 23 mm was also seen. Massive amount of fluid was detected in perihepatic, perispleenic, and the cul-de-sac area and also between bowels. Based on these findings a ruptured heterotopic pregnancy was suspected and emergency laparotomy was performed. At laparotomy, there was 800 ml of hemoperitoneum. There was a 2-3 cm ruptured isthmic ectopic pregnancy in the left tube. A left total salpingectomy was performed. Postoperative recovery was uneventful and the patient was discharged on postoperative day 3 in good condition. She was following up in the antenatal unit and the twin pregnancy is progressing normally. Heterotopic pregnancies are rare but life-threatening conditions, therefore it should be kept it in mind when a pregnant woman who underwent IVF-ET, presents low abdominal pain.